Interpersonal Processes in the Anxiety Disorders: Implications for Understanding Psychopathology and Treatment. 2010
DOI: 10.1037/12084-008
|View full text |Cite
|
Sign up to set email alerts
|

Interpersonal aspects of panic disorder and agoraphobia.

Abstract: attack come on. This avoidance may be relatively subtle-for example, the man with panic disorder who gives up running because his rapid heartbeat makes him feel like he is panicking or having a heart attack. Or it may be highly obvious-for example, the woman who becomes afraid to leave her home unless she is accompanied by a trusted person who will take care of her should she panic. When avoidance is significant, the person is said to have panic disorder with agoraphobia, for which the lifetime prevalence is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…When PD patients were classified using the DSM-IV definition of agoraphobia (American Psychiatric Association, 2000), IIP-C reflected subgroup differences in the global severity of interpersonal dysfunctions, with the agoraphobic group evidencing the greatest difficulty. This finding complements previous reports on the associations between agoraphobia and interpersonal conflicts (Chambless, 2010), suggesting that agoraphobia is associated with a higher level of general interpersonal distress. The symptom-based clusters, however, could not be discriminated by core interpersonal problems, and therefore are not associated with distinct interpersonal profiles.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…When PD patients were classified using the DSM-IV definition of agoraphobia (American Psychiatric Association, 2000), IIP-C reflected subgroup differences in the global severity of interpersonal dysfunctions, with the agoraphobic group evidencing the greatest difficulty. This finding complements previous reports on the associations between agoraphobia and interpersonal conflicts (Chambless, 2010), suggesting that agoraphobia is associated with a higher level of general interpersonal distress. The symptom-based clusters, however, could not be discriminated by core interpersonal problems, and therefore are not associated with distinct interpersonal profiles.…”
Section: Discussionsupporting
confidence: 90%
“…Although PD with agoraphobia may be associated with higher interpersonal distress than PD without agoraphobia (Chambless, 2010), according to the pathoplasticity model we did not expect the prevalent symptom-based clustering for evaluating heterogeneity in PD on the basis of the presence of agoraphobia symptoms to suffice for evaluating distinct interpersonal clusters in PD. Specifically, symptom-based clustering is not predicted to yield sufficient information for discriminating heterogeneity in interpersonal dysfunctions in patients with PD because previous studies have shown that clusters of interpersonal dysfunctions were generally unrelated to psychopathology and functional severity (Cain at el., 2010;Przeworski et al, 2011).…”
mentioning
confidence: 88%
“…Furthermore, poorer marital adjustment has been shown to predict increased likelihood of relapse, percent days abstinent, and time to relapse among people with substance use problems in treatment (e.g., Fals-Stewart, O’Farrell, & Hooley, 2001). Likewise, poorer relationship adjustment predicts poorer outcome of exposure treatment for agoraphobia (for a review, see Chambless, 2010) and treatments for generalized anxiety disorder (e.g., Durham, Allan, & Hackett, 1997; Zinbarg, Lee, & Yoon, 2007).…”
Section: Relationship Discord and The Treatment Of Psychopathologymentioning
confidence: 99%
“…Likewise, poorer relationship adjustment predicts poorer outcome of exposure treatment for agoraphobia (for a review, see Chambless, 2010) and treatments for generalized anxiety disorder (e.g., Durham, Allan, & Hackett, 1997;Zinbarg, Lee, & Yoon, 2007).…”
Section: Relationship Discord and The Treatment Of Psychopathologymentioning
confidence: 99%
“…Panic disorder provides fertile ground for the effects of EE/PC. The onset of panic disorder frequently occurs in a context of interpersonal stress (see review by Chambless, 2010). Once the disorder is established, panic disorder may strain the patient-relative relationship: When patients are agoraphobic, they may require relatives’ assistance for many aspects of daily living and may restrict family life because of their phobic avoidance.…”
mentioning
confidence: 99%